Development of A Web-Based Online Sales Information System for A Micro-Retail Store: A Case Study at Toko Sembako Doa Ibu - Ariansyah, Irgi; Rakhim Setya Permana, Basuki; Auliana, Sigit (ARRUS Journal of Engineering and Technology, 2025)
Doa Ibu Grocery Store is a micro-enterprise that still performs its sales processes manually, including transaction recording, inventory management, and sales reporting. This condition leads to several issues, such as recording errors, limited customer reach, and inefficient operations. This research aims to design and implement a web-based online sales information system to automate transaction processes, expand service reach through online ordering, and provide structured sales reports. The system development method used is the waterfall model, consisting of analysis, design, implementation, testing, and evaluation stages. The system was developed using a PHP-based digital framework, MySQL database, and integrated with Midtrans as the payment gateway. Blackbox testing was applied to ensure that the system functions according to user requirements identified through elicitation stages. The results show that the system can automatically record transactions, manage product and customer data, generate sales reports, and support online orders and order status notifications. The system is considered feasible for implementation and provides a positive impact on the efficiency and modernization of Doa Ibu Grocery Store's operations.